An early-strength rapid-setting lightweight concrete material, a preparation method and application thereof
Patent Information
- Application Number
- CN202311180079.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-09-13
AI Technical Summary
[0004]上述轻质混凝土材料并未关注如何改善早期强度特别是2h早期强度等问题
[0027]采用本发明的配方体系能够获得较佳流动度的混凝土材料,使该材料具有较好的施工性,同时轻质骨料聚苯乙烯泡沫球能够良好的分散均匀,避免团聚或漂浮于料浆上层等现象,而且所得轻质混凝土材料具有速凝、早强的特点,特别是具有较佳的2h早期强度,利于提高施工效率。此外,本发明提供的混凝土材料,其固废用量大,可有效解降低材料成本,同时解决固废堆积问题;同时该材料制备工艺简单,具有实用性和工业可行性。
Smart Images

Figure BDA0004446927710000101 
Figure BDA0004446927710000111 
Figure BDA0004446927710000112
Abstract
Description
Technical Field
[0001] This invention relates to the field of concrete materials technology, specifically to an early-strength, rapid-setting, lightweight concrete material, its preparation method, and its application. Background Technology
[0002] Chinese patent application CN 105523740 A discloses a thermally insulating lightweight concrete material and its preparation method, which is made from the following components: 350-370 parts of composite silicate cement, 70-74 parts of fly ash, 200-224 parts of water, 207.0-250.7 parts of ceramsite, 307.3-361.1 parts of ceramsite sand, and 131.7-154.7 parts of sand. This material has high compressive strength, low dry apparent density, good thermal insulation performance, and strong water resistance. This material possesses the characteristics of thermal insulation, heat insulation, lightweight, earthquake resistance, and water resistance.
[0003] Chinese patent application CN 115784690 A discloses a high-temperature resistant EPS concrete material for improving the anisotropy of 3D printing and its preparation method. The concrete material is obtained by uniformly mixing cementitious materials, water, thickener, water-reducing agent, expansion agent, polystyrene foam aggregate and mixed micro-nano inorganic fibers. The cementitious material is a cementitious system composed of 100 parts of ordinary Portland cement, 30-40 parts of rapid-hardening cement, 25-30 parts of fly ash and 6-8 parts of silica fume by mass.
[0004] The aforementioned lightweight concrete materials do not address issues such as how to improve early strength, especially 2-hour early strength. Summary of the Invention
[0005] This invention provides an early-strength, rapid-setting lightweight concrete material, its preparation method, and its application. Based on the formulation system of this invention, an early-strength, rapid-setting lightweight concrete material with good early strength, especially 2-hour strength, can be provided.
[0006] To achieve its objective, the present invention provides the following technical solution:
[0007] This invention provides an early-strength, rapid-setting lightweight concrete material, which is prepared by means of raw materials comprising the following components, in parts by weight:
[0008] 10-75 parts aluminate cement, 15-80 parts high-calcium minerals, 0.01-2 parts retarder, 0.001-2 parts water-reducing agent, 0.01-0.5 parts thickener, 0.01-1 parts adhesive powder, and 0.1-5 parts polystyrene foam aggregate;
[0009] The free calcium oxide content in the high-calcium mineral is 2-40 wt%, preferably 5-20 wt%.
[0010] The mass ratio of the aluminate cement to the high-calcium mineral is 5:1-40;
[0011] The retarder is an organic acid containing carboxylate.
[0012] In the formulation system of this invention, the components work together, and high-calcium minerals with a specific free calcium oxide content and aluminate cement are added, while the ratio of the two is controlled. At the same time, an organic acid retarder containing carboxyl groups is introduced. Through the interaction between the components in the formulation system, the setting time can be adjusted, and the early strength can be improved, especially the 2-hour early strength. The formulation system also uses water-reducing agents, thickeners, adhesive powder and polystyrene foam aggregate. Through the interaction of the components, the material density can be controlled, and early-strength, fast-setting, lightweight concrete materials can be obtained.
[0013] In the lightweight concrete material formulation system of this invention, high-calcium minerals and carboxylate-containing retarders have a certain synergistic effect with aluminate cement. By adding high-calcium minerals to aluminate cement and then compounding with carboxylate-containing retarders, the setting time can be effectively controlled by adjusting the ratio of aluminate cement to high-calcium minerals. Simultaneously, the early strength of the lightweight concrete material is not reduced but rather improved. This is completely different from the effect of adding retarders to cementitious materials in the past. Conventional methods of adding retarders to cementitious materials can prolong the setting time, but the early strength is also greatly reduced. The formulation system of this invention, based on the above ternary component system, simultaneously adds components such as polystyrene foam aggregate. Through the interaction between these components, a lightweight concrete material with early strength and rapid setting can be obtained.
[0014] By using the above-mentioned formulation system of the present invention, and by combining the components in the formulation system according to a specific dosage ratio, a fast-setting and early-strength lightweight concrete material can be obtained.
[0015] In a preferred embodiment, the retarder is tartaric acid.
[0016] In this invention, high-calcium minerals refer to minerals with a high content of free calcium oxide, specifically high-calcium minerals with a free calcium oxide content of 2-40 wt%, more preferably 5-20 wt%. In some embodiments, the high-calcium minerals are selected from one or more of tourmaline slag, fly ash, limestone, and gypsum that meet the above-mentioned free calcium oxide content requirements. Preferably, the fly ash is selected from circulating fluidized bed fly ash. It should be noted that not all minerals, such as not all fly ash, contain free calcium oxide that meets the above-mentioned content requirements. For example, although general pulverized coal boiler fly ash is high-calcium fly ash with a calcium content of 5% or even 10%, using such fly ash cannot achieve the above-mentioned synergistic effect of this invention; because the calcium oxide in pulverized coal boiler fly ash is mainly inert calcium oxide, and its free calcium oxide content is difficult to reach 2%-40%. In circulating fluidized bed fly ash, calcium oxide mainly exists as free calcium oxide. Using circulating fluidized bed fly ash with a free calcium oxide content of 2-40% can have a synergistic effect with aluminate cement and carboxylate-containing retarders. Furthermore, the inventors of this application have discovered that the free calcium oxide content of high-calcium minerals should not be too high; for example, exceeding 40% can easily lead to agglomeration of polystyrene foam aggregate and issues with concrete stability, such as cracking.
[0017] In some embodiments, the water-reducing agent is selected from one or more of naphthalene-based water-reducing agents, polycarboxylate water-reducing agents, and lignin-based water-reducing agents, with polycarboxylate water-reducing agents being preferred.
[0018] In a preferred embodiment, the thickener is selected from hydroxypropyl methylcellulose with a viscosity ≥ 50000 mPa·s. The viscosity of hydroxypropyl methylcellulose can be measured using a viscometer. In the formulation system of the present invention, using hydroxypropyl methylcellulose with a viscosity ≥ 50000 mPa·s as a thickener, combined with other components in the formulation system, facilitates the uniform distribution of polystyrene foam aggregate in the system, while preventing problems such as material bleeding and segregation.
[0019] In a preferred embodiment, the adhesive powder is selected from renewable latex powder, and more preferably the adhesive powder is 4036N type renewable latex powder, such as Wacker Chemie 4036N adhesive powder from Germany.
[0020] In a preferred embodiment, the particle size of the polystyrene foam aggregate is ≤5mm. The use of polystyrene foam aggregate with the preferred particle size in the formulation system of this invention facilitates the acquisition of early-strength, rapid-setting, lightweight concrete materials with better strength.
[0021] In some preferred embodiments, the early-strength, rapid-setting lightweight concrete material is prepared by means of the following components by weight: 10-50 parts aluminate cement, 15-50 parts high-calcium minerals, 0.1-0.5 parts retarder, 0.1-2 parts water-reducing agent, 0.1-0.5 parts thickener, 0.1-1 parts adhesive powder, and 0.1-5 parts polystyrene foam aggregate; wherein the free calcium oxide content in the high-calcium minerals is 5-20 wt%; and the mass ratio of the aluminate cement to the high-calcium minerals is 5:2.5-20. The lightweight concrete material prepared using this preferred embodiment not only has an initial setting time of less than 60 minutes, but also exhibits superior 2-hour compressive strength.
[0022] This invention also provides a method for preparing the early-strength, rapid-setting lightweight concrete material described above, comprising the following steps:
[0023] The raw materials are mixed with water to obtain the early-strength, quick-setting, lightweight concrete material; wherein the amount of water used is 0.2-0.9 times the total mass of the aluminate cement and the high-calcium minerals, for example, 0.2, 0.3, 0.5, 0.6, 0.8, 0.9 times, etc.
[0024] The early-strength, rapid-setting lightweight concrete material provided by this invention has a flowability of 360-430mm, an initial setting time of ≤60min, a final setting time of ≤120min, and a 2h compressive strength of ≥0.1MPa.
[0025] The present invention also provides an application in which the early-strength, rapid-setting, lightweight concrete material described above or the early-strength, rapid-setting, lightweight concrete material prepared by the preparation method described above is applied to thermal insulation wall materials or concrete 3D printing.
[0026] The technical solution provided by this invention has the following beneficial effects:
[0027] The formulation system of this invention can produce concrete materials with better fluidity, resulting in better workability. Simultaneously, the lightweight aggregate polystyrene foam balls can be well and uniformly dispersed, avoiding agglomeration or floating on the surface of the slurry. Furthermore, the resulting lightweight concrete material exhibits rapid setting and early strength, particularly with excellent 2-hour early strength, which is beneficial for improving construction efficiency. In addition, the concrete material provided by this invention has a large solid waste content, effectively reducing material costs and solving the problem of solid waste accumulation. Moreover, the preparation process of this material is simple, possessing practicality and industrial feasibility. Detailed Implementation
[0028] To facilitate understanding of the present invention, the following description, in conjunction with embodiments, will further illustrate the invention. It should be understood that the following embodiments are merely for a better understanding of the invention and do not imply that the invention is limited to these embodiments.
[0029] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in this technical field can be followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0030] The present invention will be illustrated below with reference to specific embodiments.
[0031] The detection methods involved in the examples or comparative examples are described below:
[0032] Initial setting time: Tested according to GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures";
[0033] Final setting time: Tested according to GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures";
[0034] 2-hour compressive strength: tested according to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete";
[0035] The method for detecting free calcium oxide in high-calcium minerals is as follows: the test shall be conducted in accordance with GB / T 176-2017 "Chemical Analysis Methods for Cement";
[0036] Flowability: The flowability test method specified in GB / T 50448-2015 "Technical Specification for Application of Cement-based Grouting Materials" was used for determination.
[0037] Dry density: The dry apparent density was determined by the integral specimen drying method in accordance with the "Technical Standard for Application of Lightweight Aggregate Concrete" (JGJ / T12-2019).
[0038] In the following embodiments, unless otherwise specified, "parts" refers to parts by mass.
[0039] Example 1
[0040] This embodiment provides an early-strength, rapid-setting lightweight concrete material.
[0041] (1) The raw materials used are described below:
[0042] High-calcium minerals: circulating fluidized bed fly ash with an average particle size of 18.9 micrometers. Its main components include 20.2 wt% SiO2, 10.5 wt% Al2O3, 43.3 wt% CaO (free calcium oxide and inert calcium oxide) and 8.8 wt% Fe2O3, of which the content of free calcium oxide is 20 wt%.
[0043] Cement raw materials: aluminate cement, Zhengzhou Jianai Special Aluminate Co., Ltd.;
[0044] Retarder: Tartaric acid, L+, Nanjing Steibo Trading Co., Ltd.;
[0045] Water-reducing agent: Polycarboxylate superplasticizer 530P, Nanjing Stebo Trading Co., Ltd.;
[0046] Thickener: Hydroxypropyl methylcellulose, viscosity 100,000 mPa·s, Hebei Haoshuo Chemical Co., Ltd.
[0047] Adhesive powder: Wacker Chemie 4036N type, Jinan Qiansheng Chemical Co., Ltd.;
[0048] EPS (polystyrene) foam aggregate: EPS foam granules, with a particle size of 3-5mm, Langfang Best Energy-Saving Building Materials Co., Ltd.
[0049] (2) Preparation steps of lightweight concrete materials
[0050] Mix 10 parts of aluminate cement and 40 parts of high-calcium minerals evenly, add 0.2 parts of retarder, 0.14 parts of water-reducing agent, 0.14 parts of thickener, 0.23 parts of adhesive powder, 1 part of EPS foam aggregate, and 30 parts of water. First, slowly mix the mixture in a mixer at a speed of 62±5 r / min for 15 seconds, and then quickly mix it at a speed of 125±10 r / min for 25 seconds to obtain lightweight concrete material.
[0051] Example 2
[0052] The procedure is the same as in Example 1, except that:
[0053] The high-calcium mineral used is circulating fluidized bed fly ash, with an average particle size of 17.6 micrometers, a total calcium oxide content of 8 wt%, and a free calcium oxide content of 5 wt%.
[0054] The preparation steps for lightweight concrete materials are as follows:
[0055] According to the proportions of each component listed in Table 1, aluminate cement and high-calcium minerals are mixed evenly, and retarder, water-reducing agent, thickener, adhesive powder, EPS foam aggregate and water are added. The mixture is first slowly stirred at a speed of 62±5 r / min for 10s, and then quickly stirred at a speed of 125±10 r / min for 20s to obtain lightweight concrete material.
[0056] Example 3
[0057] The procedure is the same as in Example 1, except that:
[0058] The high-calcium mineral used is circulating fluidized bed fly ash, with an average particle size of 20 micrometers, a total calcium oxide content of 17 wt%, and a free calcium oxide content of 10 wt%.
[0059] The preparation steps for lightweight concrete materials are as follows:
[0060] According to the proportions of each component listed in Table 1, aluminate cement and high-calcium minerals are mixed evenly, and retarder, water-reducing agent, thickener, adhesive powder, EPS foam aggregate and water are added. The mixture is first slowly stirred at a speed of 62±5r / min for 20s, and then quickly stirred at a speed of 125±10r / min for 30s to obtain lightweight concrete material.
[0061] Example 4
[0062] The procedure is the same as in Example 1, except that:
[0063] The high-calcium mineral used is tourmaline slag, with an average particle size of 19.2 micrometers, a total calcium oxide content of 63 wt%, and a free calcium oxide content of 40 wt%.
[0064] The preparation steps for lightweight concrete materials are as follows:
[0065] According to the proportions of each component listed in Table 1, aluminate cement and high-calcium minerals are mixed evenly, and retarder, water-reducing agent, thickener, adhesive powder, EPS foam aggregate and water are added. The mixture is first slowly stirred at a speed of 62±5r / min for 20s, and then quickly stirred at a speed of 125±10r / min for 30s to obtain lightweight concrete material.
[0066] Example 5
[0067] The procedure is the same as in Example 1, except that:
[0068] The high-calcium mineral used is limestone, with an average particle size of 21 micrometers, a total calcium oxide content of 56 wt%, and a free calcium oxide content of 2 wt%.
[0069] The preparation steps for lightweight concrete materials are as follows:
[0070] According to the proportions of each component listed in Table 1, aluminate cement and high-calcium minerals are mixed evenly, and retarder, water-reducing agent, thickener, adhesive powder, EPS foam aggregate and water are added. The mixture is first slowly stirred at a speed of 62±5r / min for 20s, and then quickly stirred at a speed of 125±10r / min for 30s to obtain lightweight concrete material.
[0071] Comparative Example 1
[0072] The procedure was carried out in accordance with Example 1, except that the formulation and dosage were changed, as shown in Table 1.
[0073] Experimental results: The fluidity of the slurry obtained in this comparative example was 480 mm, which was too high. Compared with Examples 1-5, this comparative example showed that the EPS foam aggregate floated on the upper layer, and the foam aggregate was difficult to distribute evenly.
[0074] Comparative Example 2
[0075] The procedure was carried out in accordance with Example 1, except that 8 parts of EPS foam aggregate were added.
[0076] Results: The prepared lightweight concrete had low early strength due to uneven EPS mixing.
[0077] Comparative Example 3
[0078] The procedure was carried out in accordance with Example 1, except that the high-calcium mineral used was fly ash from a pulverized coal furnace, with a total calcium oxide content of 13 wt% and a free calcium oxide content of 1 wt%.
[0079] Comparative Example 4
[0080] The procedure was carried out in accordance with Example 1, except that the free calcium oxide content of the high-calcium mineral used was 45 wt%.
[0081] Experimental results: This comparative example used high-calcium minerals with excessively high free calcium oxide content. Compared with the examples, the flowability of this comparative example was 330 mm. Compared with Examples 1-5, the EPS aggregate in this comparative example showed severe agglomeration and could not be evenly distributed.
[0082] Comparative Example 5
[0083] The procedure was carried out in accordance with Example 1, except that: the amount of aluminate cement was 45 parts, the amount of high-calcium mineral was 4.5 parts, and the mass ratio of aluminate cement to high-calcium mineral was 5:0.5.
[0084] Comparative Example 6
[0085] The procedure was carried out in accordance with Example 1, except that: the amount of aluminate cement was 5 parts, the amount of high-calcium mineral was 45 parts, and the mass ratio of aluminate cement to high-calcium mineral was 5:45.
[0086] Comparative Example 7
[0087] The procedure was carried out in accordance with Example 1, except that no retarder was added.
[0088] Comparative Example 8
[0089] The procedure was carried out in accordance with Example 1, except that tartaric acid was replaced with citric acid.
[0090] Comparative Example 9
[0091] The procedure was carried out in accordance with Example 1, except that aluminate cement was replaced with silicate cement (Diamond brand P·O42.5R, Yanshan Holding Group Co., Ltd.).
[0092] Comparative Example 10
[0093] The procedure was carried out in accordance with Example 1, except that aluminate cement was replaced with sulfoaluminate cement (425 grade sulfoaluminate cement, Henan Nuoji Building Materials Co., Ltd.).
[0094] Table 1 Formula Table
[0095]
[0096]
[0097] Table 2. Experimental results of Examples 1-5, Comparative Examples 2-3, and Comparative Examples 5-10
[0098]
[0099] During the processes of Examples 1-5, the fluidity of the resulting slurry was between 360-430 mm, and the foamed aggregate and all components were well and uniformly mixed without any foamed aggregate floating on the surface of the slurry or agglomerating. Furthermore, the initial setting time of the resulting materials was ≤60 min, the final setting time was ≤120 min, and they exhibited good 2-hour compressive strength. The materials obtained in Examples 1-5, after dry density testing, had a dry density of 432-789 kg / m³. 3 It can be used as a lightweight material.
[0100] Compared with Example 1, Comparative Example 2 had 8 parts of EPS foam aggregate added to the formulation system, which significantly reduced the fluidity and also significantly reduced the 2-hour compressive strength.
[0101] Compared with Example 1, the free calcium oxide content in the high-calcium mineral used in Comparative Example 3 was less than 2%, and the initial setting time and final setting time of the resulting material were significantly longer. The resulting material did not have 2-hour early strength.
[0102] Compared with Comparative Examples 5-6 and Example 1, the amount of aluminate cement was not 10-75 parts, the amount of high-calcium mineral was not 15-80 parts, and the mass ratio of aluminate cement to high-calcium mineral was not 5:1-40. The initial setting time and final setting time of the resulting material were significantly longer, and it did not have 2-hour compressive strength.
[0103] Compared with Comparative Example 7, which did not add a retarder, Example 1 had a significantly shorter initial setting time and better early strength. This shows that the role of the retarder in the formulation system of this invention is significantly different from the role of adding a retarder to cement-based materials in the prior art.
[0104] It is readily understood that the above embodiments are merely illustrative examples for clear explanation and do not imply that the invention is limited thereto. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A type of early-strength, rapid-setting, lightweight concrete material, characterized in that, It is prepared from raw materials comprising the following components, in parts by weight: 10-75 parts aluminate cement, 15-80 parts high-calcium minerals, 0.01-2 parts retarder, 0.001-2 parts water-reducing agent, 0.01-0.5 parts thickener, 0.01-1 parts adhesive powder, and 0.1-5 parts polystyrene foam aggregate; The free calcium oxide content in the high-calcium mineral is 2-40 wt%. The mass ratio of the aluminate cement to the high-calcium mineral is 5:1-40; The retarder is tartaric acid.
2. The early-strength, rapid-setting, lightweight concrete material according to claim 1, characterized in that, The free calcium oxide content in the high-calcium mineral is 5-20 wt%.
3. The early-strength, rapid-setting, lightweight concrete material according to claim 1, characterized in that, The high-calcium mineral is selected from one or more of tourmaline slag, fly ash, limestone, and gypsum.
4. The early-strength, rapid-setting, lightweight concrete material according to claim 3, characterized in that, The fly ash is selected from circulating fluidized bed fly ash.
5. The early-strength, rapid-setting, lightweight concrete material according to any one of claims 1-4, characterized in that, The water-reducing agent is selected from one or more of naphthalene-based water-reducing agents, polycarboxylate-based water-reducing agents, and lignin-based water-reducing agents.
6. The early-strength, rapid-setting, lightweight concrete material according to claim 5, characterized in that, The water-reducing agent is selected from polycarboxylate water-reducing agents.
7. The early-strength, rapid-setting, lightweight concrete material according to any one of claims 1-4, characterized in that, The thickener is selected from hydroxypropyl methylcellulose with a viscosity ≥ 50000 mPa•s.
8. The early-strength, rapid-setting, lightweight concrete material according to any one of claims 1-4, characterized in that, The adhesive powder is selected from renewable latex powder; And / or, the particle size of the polystyrene foam aggregate is ≤5mm.
9. The early-strength, rapid-setting, lightweight concrete material according to claim 8, characterized in that, The adhesive powder is 4036N type renewable latex powder.
10. The early-strength, rapid-setting, lightweight concrete material according to any one of claims 1-4, characterized in that, 10-50 parts aluminate cement, 15-50 parts high-calcium minerals, 0.1-0.5 parts retarder, 0.1-2 parts water-reducing agent, 0.1-0.5 parts thickener, 0.1-1 parts adhesive powder, and 0.1-5 parts polystyrene foam aggregate; The free calcium oxide content in the high-calcium mineral is 5-20 wt%. The mass ratio of the aluminate cement to the high-calcium mineral is 5:2.5-20.
11. The method for preparing early-strength, rapid-setting lightweight concrete material according to any one of claims 1-10, characterized in that, Includes the following steps: The raw materials are mixed with water to obtain the early-strength, quick-setting, lightweight concrete material; wherein the amount of water used is 0.2-0.9 times the total mass of the aluminate cement and the high-calcium minerals.
12. The application of the early-strength, rapid-setting lightweight concrete material according to any one of claims 1-10 or the early-strength, rapid-setting lightweight concrete material prepared by the preparation method according to claim 11 in thermal insulation wall materials or concrete 3D printing.
Citation Information
Patent Citations
Thermal-insulation light concrete material and preparation method thereof
CN105523740A
High-temperature-resistant EPS concrete material for improving 3D printing anisotropy and preparation method thereof
CN115784690A
Rapid-hardening and early-strength structural reinforcement materials based on aluminate cement and steel slag
CN102295447A
Lightweight thermal-insulation prefabricated lightweight aggregate concrete and preparation method thereof
CN116693260A